Antifungal Activity and Plant Growth-Promoting Properties of Bacillus mojovensis B1302 against Rhizoctonia Cerealis - Yanjie Yi; Pengyu Luan; Kang Wang; Guiling Li; Yanan Yin; Yanhui Yang; Qingyao Zhang; Yang Liu (Microorganisms, 2022)
Rhizoctonia cerealis is a worldwide soil-borne pathogenic fungus that significantly infects wheat and causes sharp eyespot in China. However, the biocontrol strains used for the control of Rhizoctonia cerealis are insufficient. In the present study, antagonistic strain B1302 from the rhizosphere of wheat were isolated and identified as Bacillus mojovensis based on their morphological, physiological, and biochemical characteristics, and their 16S rDNA sequence. Culture filtrate of strain B1302 had a broad antifungal spectrum. In order to improve the antifungal activity of B1302, response surface methodology (RSM) was used to optimize the culture conditions. The final medium composition and culture conditions were 13.2 g/L of wheat bran, 14.1 g/L of soybean meal, 224 r/min of rotation speed, 7.50 of initial pH, and 1.5 × 108 CFU/mL of inoculation amount at 35 °C for a culture duration of 72 h. B. mojavensis B1302 inhibited the hyphae growth of R.cerealis and produced hydrolytic enzymes (protease, chitinase, and glucanase), IAA, and had N-fixing potentiality and P-solubilisation capacity. It can also promote wheat seedling growth in potted plants. The disease incidence and index of wheat seedlings were consistent with the effect of commercial pesticides under treatment with culture filtrate. The biocontrol efficacy of culture filtrate was significant—up to 65.25%. An animal toxicological safety analysis suggested that culture filtrate was safe for use and could be developed into an effective microbial fungicide to control wheat sharp eyespot.